Diagnosing and grading heart failure with tomographic perfusion lung scintigraphy: validation with right heart catheterization. (17th July 2018) - Jögi, Jonas; Al‐Mashat, Mariam; Rådegran, Göran; Bajc, Marika; Arheden, Håkan
Abstract: Aims: Pulmonary congestion remains a diagnostic challenge in patients with heart failure (HF). The recommended method, chest X‐ray (CXR), lacks in accuracy, whereas quantitative tomographic lung scintigraphy [ventilation/perfusion single‐photon emission computed tomography (V/P SPECT)] has shown promising results but needs independent validation. The aim of this study is to evaluate V/P SPECT as a non‐invasive method to assess and quantify pulmonary congestion in HF patients, using right heart catheterization as reference method. The secondary objective was to investigate the performance of V/P SPECT in the clinical setting compared with CXR. Methods and results: Forty‐six consecutive patients with HF that were under consideration for heart transplantation were studied prospectively. All participants were examined with V/P SPECT, CXR, and right heart catheterization. Pulmonary artery wedge pressure served as reference method. Quantitative perfusion gradients were derived from V/P SPECT images. Ventilation/perfusion single‐photon emission computed tomography images were also assessed both by expert readers and clinical nuclear medicine physicians. Expert readers correctly identified 87% of all patients with an elevated pulmonary artery wedge pressure > 15 mmHg. The average sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for V/P SPECT assessed by the expert readers were 87%, 72%, 85%, and 75%, respectively. In the clinical nuclear medicine setting, V/P SPECT had 87% sensitivity, 63% specificity, 81% PPV, and 71% NPV. Clinically, V/P SPECT outperformed CXR, which had 27% sensitivity, 75% specificity, 67% PPV, and 35% NPV. Conclusions: Ventilation/perfusion single‐photon emission computed tomography can be used as a non‐invasive method to diagnose and quantify pulmonary congestion in patients with HF and is more accurate than CXR in diagnosing pulmonary congestion in the clinical setting.